Transport of indium, gallium and thallium metal ions through chromatographic fiber supported solid membrane in acetylacetone containing mixed solvents - Gaikwad, Abaji G. (Chinese Journal of Chemical Engineering, 2011)
The transport of metal ions of indium, gallium and thallium from source solution to receiving phase through the chromatographic fiber supported solid membrane in the acetylacetone (HAA) containing mixed solvent system has been explored. The fibers supported solid membranes were prepared with chemical synthesis from cellulose fibers and citric acid with the carboxylic acid ion exchange groups introduced. The experimental variables, such as concentration of metal ions (10(-2) to 10(-4) mol.L(-1)) in the source solution, mixed solvent composition [for example, acetylacetone, (2,4-pentanedione), (HAA) 20% (by volume), 1,4-dioxane 10% to 60% and HCl 0.25 to 2 mol.L(-1)] in the receiving phase and stirring speed (50-130 r.min(-1)) of the bulk source and receiving phase, were explored. The efficiency of mixed solvents for the transport of metal ions from the source to receiving phase through the fiber supported solid membrane was evaluated. The combined ion exchange solvent extraction (CIESE) was observed effective for the selective transport of thallium, indium and gallium metal ions through fiber supported solid membrane in mixed solvents. The oxonium salt formation in the receiving phase enhances thallium, indium and gallium metal ion transport through solid membrane phase. The selective transport of thallium metal ions from source phase was observed from indium and gallium metal ions in the presence of hydrochloric acid in organic solvents in receiving phase. The separation of thallium metal ions from the binary mixtures of Be(II), Ti(IV), Al(III), Ca(II), Mg(II), K (I), La(III) and Y(III) was carried out in the mixed solvent system using cellulose fiber supported solid membrane.
Keywords: acetylacetone; extraction; fiber supported solid membrane; metal ions transfer; stripping

Transport of metal ions through cellulose fiber supported solid membrane into tributyl phosphate containing mixed solvents - Gaikwad, Abaji G. (Chemical and Biochemical Engineering Quarterly, 2011)
A novel cation exchange fiber supported solid membrane was developed for transport of cobalt, manganese and nickel metal ions. Fiber supported solid membrane was prepared by chemically modifying the cellulose fibers with citric acid. In the fiber supported solid membrane, the diffusion by capillary action by keeping the liquid phase in the porous solid fiber and ion exchange mechanism were used for the effective transport of metal ions. The experimental variables examined were concentration of metal ions (10(-2) to 10(-4) mol L-1) in the source solution, mixed solvent composition (phi = 20 % TBP, acetone or tetrahydrofuran or 1,4-dioxane or methanol or ethanol or 2-propanol 10 to 60 % and HCl (1 to 2 mol L-1) in the receiving phase and stirring speed (40-120 rpm) of the bulk source and receiving phase. The enrichment of concentration of cobalt, manganese and nickel metal ions was observed from the dilute solutions.
Keywords: binary of mixtures of metal ions; cobalt; extraction; fiber supported solid membrane; ion exchange; manganese and nickel metal ions; stripping

Transport of metal ions through fiber supported solid membranes in mixed solvents - Gaikwad, Abaji G. (Fibers and Polymers, 2011)
The transport of metal ions has been explored of bismuth, cadmium and lead from source solution to receiving phase through the fiber supported solid membrane system. The fibers supported solid membranes were prepared by chemically modification of cellulose fibers with the introducing the ion exchanging groups. The experimental variables explored were concentration of metal ions in the source solution, mixed solvent composition in the receiving phase and stirring speed of the bulk source solution and receiving phase. The efficiency has been evaluated for the transport of metal ions from the source to receiving phase through the fiber supported solid membrane. The pre-concentration was investigated of metal ions from the dilute solutions. The fiber supported solid membrane with two-channel systems had been investigated for the transport of metal ions from the source to receiving phase. The capillary action phenomenon helps to effectively transport the metal ions through the fiber supported solid membrane.
Keywords: binary of mixtures of metal ions; Bismuth; Cadmium and lead metal ions; extraction; fiber supported solid membrane; ion exchange; stripping